Metal Patch Testing with Nickel, Chromium, and Cobalt in Atopic Dermatitis Patients - Yuri Widia; Evy Ervianti; Marsudi Hutomo (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Atopic dermatitis (AD) is a cutaneous inflammation characterized by skin hyperreactivity due to complex interplay between genetic susceptibility and environmental allergens. In AD, recurrences are frequent and cause problems. Although elevation of total immunoglobulin E (IgE) level; and positive specific IgE to environmental allergens and food are found in most cases, some AD patients with normal IgE level still recurred and raised the possibility of other factors as a trigger. Datas from some studies showed high frequency of positive results in metal patch testing and improvement in AD after allergen  elimination and low metals diet. Based on these studies, metal is considered as a trigger of reccurrences in AD. Nickel, chromium and cobalt are the primary metals that gives high frequency of positive patch test results in patients with intrinsic AD. Purpose: To evaluate metal patch testing results with nickel, chromium and cobalt in atopic dermatitis patients at Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya. Methods: This study was observational cross-sectional descriptive study of patch testing to nickel, chromium, and cobalt at 23 AD patients who met the inclusion and exclusion criteria. Results: Patch testing to nickel sulphate metal gave positive result in 17.39% patients, potassium dichromate 8.7%, and cobalt chloride 4.35%. Four people (17.39%) showed positive patch test results; 3 people (13.04%) showed the value of the normal serum total IgE and 1 (4.35%) showed an increasing total serum IgE level. Conclusions: Metal patch testing against AD can be considered in AD patients with normal IgE values.